Agroforestry and permaculture as tools to improve farmers’ well-being - Fromonteil, Bastien (2018)
Agriculture has been on the spotlight in the recent years: main sector responsible for global warming, food scandals, rural desertification… But this has consequences for the farmers themselves, who are throughout the world above other professions when it comes to suicide rate, which makes the question of farmer wellbeing central. Agroecology has been praised worldwide for its positive effects on the environment, on health, but also on the economic situation of farmers. But although agroecology has been defined as a comprehensive framework, encompassing all the value-chain of agriculture, no research has been made on the effect of agroecology on the well-being of farmers. Through interviewing groups of farmers that switched from conventional agriculture to agroecology, I showed that agroecology has a significant impact on the well-being of farmers, by increasing: their sense of purpose through aligning their values with how they act; their control over their own lives and environment because they truly master their culture and agroecology helps reduce the dependence towards the supply-chain, and the personal growth they experience by the time they dedicate outside of work to other activities and the creativity agroecology demands when it comes to adaptation to the characteristics of the crops / the field. Therefore, farming is made more attractive and can be part of state policies in order to revitalize rural areas.